Traumatic brain injury and hazardous/harmful drinking: Concurrent and single associations with poor mental health and roadway aggression. (February 2019) - Ilie, Gabriela; Wickens, Christine M.; Ialomiteanu, Anca; Adlaf, Edward M.; Asbridge, Mark; Hamilton, Hayley; Mann, Robert E.; Rehm, Jürgen; Rutledge, Robert; Cusimano, Michael D.
Highlights: Men at higher risk of history of brain injury, hazardous-drinking or both compared to women. Younger adults more at risk of both conditions, concurrently, compared to older adults. Adults in one or both conditions had greater odds of mental health and roadway aggression. Abstract: This study describes the association among lifetime traumatic brain injury (TBI) and past year hazardous/harmful drinking, as well as their unique and synergistic effects, on mental health problems and roadway aggression among Canadian adults. A cross-sectional sample of 6074 Ontario adults aged 18 years or older were surveyed between 2011 and 2013. TBI was defined as trauma to the head resulting in loss of consciousness or overnight hospitalization. Past year hazardous/harmful drinking was assessed using the Alcohol Use Disorders Identification Test. An estimated 13.1% (95%CI:12.0, 14.2) adults reported a prior TBI (no hazardous/harmful drinking), 2.7% (95%CI:2.2, 3.3) reported a prior TBI while concurrently screening positive for past year hazardous/harmful drinking and 9.8% (95%CI:8.9, 10.9) screened positive for hazardous/harmful drinking (no TBI). Men had significantly higher odds of exhibiting all three conditions compared to women, especially for the concurrent class. Younger adults had significantly greater odds of hazardous/harmful drinking, or the concurrent class compared to adults 55 years and older. Adults in any of the three conditions had greater odds for mental health problems and roadway aggression. Concordance of both conditions corresponded to a greater than additive effect and greater odds of mild roadway aggression, than either condition alone. Results show that singly and jointly, these conditions are associated with adverse health and behavioral impediments.